2013
DOI: 10.2139/ssrn.2280214
|View full text |Cite
|
Sign up to set email alerts
|

Negative Campaigning, Fundraising, and Voter Turnout: A Field Experiment

Abstract: JEL classification: D72 C93 M37 Keywords:Voter turnout Negative campaigning Comparative advertising Fundraising Field experiment a b s t r a c t Why do candidates risk alienating voters by engaging in negative campaigning? One answer may lie in the large empirical literature indicating that negative messages are more effective than positive messages in getting individuals to do many things, including voting and purchasing goods. Few contributions to this literature, however, gather data from a field environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…field "Given the large variance in business performance at baseline, the number of samples needed to detect 10% change in business performance with 90% statistical power is over one thousand, which is far beyond our training and survey budget." Barton et al (2016) field "We performed initial power calculations for the districts pooled, which indicated that we would detect a 5 percent difference in turnout rates at p = 0.05 between the negative and positive groups with a power of 0.85. When looking at each district individually, however, the effect size needs to be roughly ten percentage points to have an 80% chance of finding it at p = 0.05.…”
Section: Appendix 4 Power / Sample Size Calculations In Jebomentioning
confidence: 99%
“…field "Given the large variance in business performance at baseline, the number of samples needed to detect 10% change in business performance with 90% statistical power is over one thousand, which is far beyond our training and survey budget." Barton et al (2016) field "We performed initial power calculations for the districts pooled, which indicated that we would detect a 5 percent difference in turnout rates at p = 0.05 between the negative and positive groups with a power of 0.85. When looking at each district individually, however, the effect size needs to be roughly ten percentage points to have an 80% chance of finding it at p = 0.05.…”
Section: Appendix 4 Power / Sample Size Calculations In Jebomentioning
confidence: 99%
“…The possibility that different forms of information can have different impacts has been extensively analysed in the literatures assessing the effects of negative and positive campaigns or advertising on political behaviour (Ansolabehere et al 1994;Lau et al 2007;Fridkin and Kenney 2011;Barton et al 2016), on consumer decisions (Levin 1987), on health related behaviour (Meyerowitz and Chaiken 1987), and on environmental choices (Spence and Pidgeon 2010). While our experiment compares neutral and charged information treatments, rather than positive and negative ones, similar theoretical arguments can be applied.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Moreover, our individual level data permits us to study heterogeneous effects for different groups of respondents, and the results indicate that information may indeed affect voter behaviour differently depending on their past voting experience. The use of two different treatments in our experiment is related to and motivated by the experimental literature on effects of negative campaigning, primarily conducted in the United States, which presents mixed results on voter turnout (Ansolabehere et al 1994;Lau et al 2007;Fridkin and Kenney 2011;Barton et al 2016). In the context of a less democratic system, our results suggest that demobilizing effects of charged information predominate.…”
Section: Introductionmentioning
confidence: 97%
“…Wintrobe 1981), job selection (Clark 1997), voting (e.g. Chari, Jones, and Marimon 1997;Barton, Castillo, and Petrie 2016), risk taking (e.g. Kanbur 1981) and compliance with authority (e.g.…”
Section: Introductionmentioning
confidence: 99%